2011
DOI: 10.1111/j.1750-3841.2010.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microstructural Properties of Coffee Beans by Synchrotron X‐Ray Microtomography: A Methodological Approach

Abstract: Synchrotron radiation microtomography is an elegant nondestructive imaging technique to investigate the microstructural properties of porous cellular matrices like the green and roasted coffee beans. The quantitative analysis of the resulting 2D and 3D images allows a more comprehensive and objective characterization of the sample under investigation as a whole or of extracted Volumes-of-Interest in the bean. This imaging technique could have a major role in understanding the effects of roasting process condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…We found that grinding soft beans resulted in higher diacetyl concentrations (at the source) than hard beans. The reasons for this finding are unclear, although it may be a result of the difference in microstructural properties between soft and hard beans, which have been reported to affect grinding and brewing performances [52] .…”
Section: Discussionmentioning
confidence: 97%
“…We found that grinding soft beans resulted in higher diacetyl concentrations (at the source) than hard beans. The reasons for this finding are unclear, although it may be a result of the difference in microstructural properties between soft and hard beans, which have been reported to affect grinding and brewing performances [52] .…”
Section: Discussionmentioning
confidence: 97%
“…Several imaging techniques, such as magnetic resonance imaging (MRI) (Ghosh, Jayas, Gruwel, & White, 2006), synchrotron X-ray fluorescence (De Jonge & Vogt, 2010), X-ray absorption (Staedler, Masson, & Schönenberger, 2013), phase contrast (Cloetens, Mache, Schlenker, & Lerbs-Mache, 2006) and neutron tomography (Cleveland IV et al, 2008), have been applied to plant and seed analysis. Among the techniques, high-resolution desktop X-ray absorption tomography (micro-CT) is highly recommended because of its excellent contrast, which allows flexibility to analyze different biological and mineral materials and it increases commercial instrumentation availability (Stuppy, Maisano, Colbert, Rudall, & Rowe, 2003;Pittia et al, 2011;Milien, Renault-Spilmont, Cookson, Sarrazin, & Verdeil, 2012;Dawson, Francis, & Carpenter, 2014;Friis, Marone, Pedersen, Crane, & Stampanoni, 2014). Unlike radiography, which is a projection image, micro-CT produces a pack of two-dimensional cross-sectional images that can be combined into a three-dimensional image allowing internal inspection and measurement (Stuppy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray computed micro-tomography (µ-CT) has been used successfully to study the structures and properties of many products including food. These include bread, cereal bars, apples, mayonnaise, coffee beans and chocolate to name a few [8][9][10][11][12][13][14][15][16][17]. The present work uses a noninvasive method, via synchrotron X-ray µ-CT to track the movement of a secondary immiscible liquid, within a model food suspension.…”
Section: Introductionmentioning
confidence: 99%